A Primer on the Methods and Applications for Contrast Echocardiography in Clinical Imaging - Seol, Sang-Hoon (Korean Society of Echocardiography, 2014)
Contrast echocardiography is broadly described as a variety of techniques whereby the blood pool on cardiac ultrasound is enhanced with encapsulated gas-filled microbubbles or other acoustically active nano- or microparticles. The development of this technology has occurred primarily in response to the need improve current diagnostic applications of echocardiography such as the need to better define left ventricular cavity volumes, regional wall motion, or the presence or absence of masses and thrombi. A secondary reason for the development of contrast echocardiography has been to expand the capabilities of echocardiography. These new applications include myocardial perfusion imaging for detection of ischemia and viability, perfusion imaging of masses/tumors, and molecular imaging. The ability to fill all of these current and future clinical roles has been predicated on the ability to produce robust contrast signal which, in turn, has relied on technical innovation with regards to the microbubble contrast agents and the ultrasound imaging paradigms. In this review, we will discuss the basics of contrast echocardiography including the composition of microbubble contrast agents, the unique imaging methods used to optimize contrast signal-to-noise ratio, and the clinical applications of contrast echocardiography that have made a clinical impact.